The Astral Summer - Petti, Ken.; Amodeo, John, 1949 May 19-; Westwood, Cassandra (New York : Grosset & Dunlap, 2005)
Having retrieved all the pieces of her gazing ball and learned that she has two powers--kani and aura sight, Zenda goes on a retreat led by her friend Persuaja to learn the value of her talents and the responsibilities that accompany them.
Accelerated Reader AR
Keywords: Fantasy